Predicting Treatment Attrition Among Seriously Violent Offenders: An Application of the Directionality Model. (August 2014) - Kroner, Daryl G.; Power, Jenelle; Takahashi, Masaru; Harris, Andrew J. R.
Treatment completion by violent offenders results in fewer victims and less violence in society. As researchers and members of society, we have a compelling interest in finding ways to keep violent male offenders in effective treatment programs. This study examines file-rated predictors of treatment attrition from an institutionally based program for persistently violent offenders. Each of the three prediction models of institutionally based treatment attrition included the predictors of motivation for assistance and prior treatment dosage: (a) the past criminal behavior model, (b) the recent antisocial behavior model, and (c) the non-antisocial instability model. Recent antisocial behavior did not improve the prediction of treatment attrition over the past criminal behavior model. Motivation for assistance did not make a contribution in the recent antisocial behavior or the non-antisocial instability models while prior treatment dosage consistently contributed to the prediction of attrition across the models. Recent non-antisocial behavior is important to offender treatment attrition.